2016
DOI: 10.1038/ncomms13251
|View full text |Cite
|
Sign up to set email alerts
|

Experimental verification of multipartite entanglement in quantum networks

Abstract: Multipartite entangled states are a fundamental resource for a wide range of quantum information processing tasks. In particular, in quantum networks, it is essential for the parties involved to be able to verify if entanglement is present before they carry out a given distributed task. Here we design and experimentally demonstrate a protocol that allows any party in a network to check if a source is distributing a genuinely multipartite entangled state, even in the presence of untrusted parties. The protocol … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
117
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(128 citation statements)
references
References 41 publications
0
117
0
Order By: Relevance
“…Therefore, our result shows a potential application for quantum metrology [32]. In addition, our results can be used for probabilistic entanglement detection [33][34][35]. Namely, we have shown that the winning probability (7) asymptotically reaches 1 for certain entangled states, whereas it asymptotically vanishes for all separable states, thus one can verify the presence of entanglement (in target state) with a very high probability even by using a single-copy of a quantum system (provided that N is sufficiently large).…”
Section: Discussionmentioning
confidence: 54%
“…Therefore, our result shows a potential application for quantum metrology [32]. In addition, our results can be used for probabilistic entanglement detection [33][34][35]. Namely, we have shown that the winning probability (7) asymptotically reaches 1 for certain entangled states, whereas it asymptotically vanishes for all separable states, thus one can verify the presence of entanglement (in target state) with a very high probability even by using a single-copy of a quantum system (provided that N is sufficiently large).…”
Section: Discussionmentioning
confidence: 54%
“…. The quality of this 'fusion' operation is however, limited by the spectral-temporal indistinguishability of the signal photons generated in each source, which can be mitigated to some extent by temperature tuning one of the sources, but limits the fidelity of the three-qubit GHZ state to 0.80±0.01 [71].…”
Section: Methodsmentioning
confidence: 99%
“…The cluster state yñ | is the state generated in our setup in the ideal case. However, due to the various dominant sources of error discussed above, including spectral and spatial imperfections introduced during the four-wave mixing process at the PCFs [65,[69][70][71], the fusion PBS between the signal photons [72], the path expansion [54] and to a lesser extent higher-order photon emissions and fibre inhomogeneity [71,72], the actual state generated is a mixed state. We therefore first characterise the quality of the cluster state generated in our setup.…”
Section: Methodsmentioning
confidence: 99%
“…Photons are becoming a necessary element of quantum information with the format of state representation and have been widely used in optical quantum information science, including quantum teleportation, one‐way quantum computation, quantum simulation, and quantum metrology . Integrated photonics has been gradually recognized as a promising platform to generate and manipulate a quantum photonic state due to the low pump power requirement, high stability, and scalability, and advantageous portability for distributed quantum networks . In various platforms for quantum photonic integrated circuits (QPICs), the silicon‐on‐insulator (SOI) technology has been considered as one of the most promising options to realize high‐quality photon‐pair sources because of its unique advantages .…”
Section: Introductionmentioning
confidence: 99%